Object-oriented CRONE toolbox for fractional differential signal processing - Malti, Rachid; Melchior, Pierre; Lanusse, Patrick; Oustaloup, Alain (Signal, image and video processing, 2012)
The CRONE toolbox, developed since the nineties by the CRONE team, is a Matlab toolbox dedicated to fractional calculus and its applications in signal processing and automatic control. It is currently evolving toward an object-oriented version, which allows many enhancements. Three main classes, dedicated to fractional system representations namely fractional transfer functions (frac_tf), fractional zeros poles and gain (frac_zpk), and fractional state-space (frac_ss), are developed. All three user classes are children of a parent class (frac_lti) that contains some common attributes of fractional systems. Among the enhancements of the object programming of the CRONE toolbox is the overloading of basic operators (+, −, ×, /, .×, …) and standard Matlab scripts (lsim, bode, nichols, …) for the new classes. As a consequence, an end-user familiar with standard Matlab operators and scripts can use straightforwardly the CRONE toolbox. The main objective of this paper is to present class diagrams and principle features of the object-oriented CRONE toolbox, which can be downloaded at http://cronetoolbox.ims-bordeaux.fr .